Equalisation and Compensation Mechanisms in the New Rome Urban Development Plan - Lorenzo Casini (Italian Journal of Planning Practice, 2014)
The adoption of equalisation and compensation mechanisms within the urban plan for Rome proved to be quite controversial. The regional law provides nearly no provisions for governing such planning tools, and the regulations set out by the plan introduce a somewhat complex system. The present paper, after a brief presentation of the history of land ownership and development within the city, will focus on the main features of equalisation and compensation practices which aim at governing the distribution of development rights among landowners and developers.